INFLUENCE OF LEADERSHIP, COMPETENCE AND CAREER DEVELOPMENT AGAINSTIMPROVEMENT IN THE EMPLOYEE PERFORMANCEDEPARTMENT OF FINANCE AND ACCOUNTING PT. HARDAYA INTI PLANTATIONS BUOL - Aqfir Aqfir; Suriani Suriani (Economy Deposit Journal (E-DJ), 2019)
This research is based on the phenomenon that shows that employees have not been able to work optimally in a company. The purpose of this study is to find out and analyze the Effects of Leadership, Competence and Career Development on Improving Employee Performance in the Finance and Accounting Department of PT. Hardaya Inti Plantations Buol Regency Branch. This research is a quantitative descriptive study with a sample size of 30 respondents, while the sampling technique used in this study is to take the entire population from employees. The instrument testing uses validity test, reliability test and classic assumption test. While the method of data analysis uses multiple linear regression analysis with t test, f test. The results of the independent leadership variable research (X1) obtainedarithmetic(1.645) <Ttable(1.706), competency variable (X2) tarithmetic (0.335) <Ttable (1.706) and career development variables (X3) tarithmetic (2.606)> Ttable (1,706). Then the leadership variable (X1) does not partially influence employee performance variables (Y), competence (X2) does not partially influence employee performance variables (Y) and career development (X3) partially influences employee performance (Y). F test results show that Farithmetic (11,007)> Ftable (2.96), and the significance level is smaller than the 5% confidence level (0,000 <0.05) then the hypothesis is accepted which means thevariables independent (leadership, competence and career development ) together or simultaneously affect thevariable dependent (employee performance) positively and significantly. And from the results of multiple linear regression analysis obtained Correlation Counsel (Multiple R) value of 0.748 or 75%. This shows that the correlation between the independent variable (leadership, competence and career development) to the dependent variable (employee performance) is equal to 0.748 or 75%.